Uṣūl al-Madhāhib al-Ṣūfīyah al-Muḥaddathah bi Indūnīsīyā: Mulāhaẓat ‘alā Kitāb Itḥāf al-Dhākī li al-Shaykh Ibrāhīm al-Kurānī - Oman Fathurahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
The present article is a philological study of one of the most important works of lbrahim al-Kurani, written in Malay-Indonesian context, that is Ithaf al-Zaki bi Sharh al-Tuhfah al-Mursalah Ila Ruh al- Nabi. Looking at the title, one can see that Ithaf al-Zaki -two of the manuscripts of which were found in the library of Dar al-Kutub al-Misriyyah, Cairo- is a commentary of the Tuhfah al-Mursalah Ila Ruh al-Nabi of al-Burhanpuri. As is mentioned above, this particular work of al-Burhanpuri had raise controversy not only among the Malay-Indonesian Muslim scholars, but also in the Muslim world in general.DOI: 10.15408/sdi.v9i1.676